PERBEDAAN EQUITY CROWDFUNDING DAN INITIAL PUBLIC OFFERING (IPO) DALAM HUKUM PASAR MODAL INDONESIA - Rahmadhani, Widya (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Equity Crowdfunding is newly known in Indonesia. Indonesia’s Financial Services Authority passed new regulation that regulating Equity Crowdfunding through Indonesia Financial Services Authorities Rule Number 37/POJK.04/2018 regarding Equity Crowdfunding. Equity Crowdfunding concept considered similar to Initial Public Offering (IPO). Further, this research objective is to analyze Equity Crowdfunding from Indonesia’s Capital Market Law Perspective to find out if Equity Crowdfunding is remarkably similar to Initial Public Offering (IPO). This research is a normative study using documentary studies in the form of secondary data. The research was found that although there are similarities on the main concept between Equity Crowdfunding and Initial Public Offering, the two has distinguishing power. The research also found that there are some risks awaiting on the Equity Crowdfunding scheme.